Manufacturing of 10 cc volumetric displacement four stroke petrol model engine cylinder block using metal casting process - Norazlin, Md. Kalil (2010)
This thesis is proposed to develop a 10 cc volumetric displacement four stroke petrol engine cylinder block using metal casting process. Since the development of the engine design getting advanced and complex, casting process also need to keep pace with those development. Thus, to enhance the casting process, control of molten metal flow, pattern design and analysis process play an important role. Therefore, this project will result in the development of casting technology using lead metal and bondcrete to simulate the alternative way of low cost casting method. As for the component to be cast, a small displacement model engine is chosen because it is more likely the same with the internal combustion for commercial vehicles but slightly different path in comparison to bigger displacement engine and easy to manufacture using modest equipment. In a small scale, the development of the complex engine is also reduce and provide important significance platform of application of casting technology for engine block development. Bondcrete casting shows a potential for an alternatives casting process but a lot of tuning needed. While lead is chosen to simulate the bondcrete casting as a molten metal due to its low melting point. It is found that melting point of lead is about 327.46 degree Celsius which is lower than aluminum. Even though there are some defect that usually experienced by other casting such as porosity, inclusion and short casting, but overall process is successfully done using low tooling cost. Based on the final product, it can be concluded that bondcrete casting can be used as an alternatives of other casting process.